Determination of confinement regime boundaries via separatrix parameters on Alcator C-Mod based on a model for interchange-drift-Alfvén turbulence - M.A. Miller; J.W. Hughes; T. Eich; G.R. Tynan; P. Manz; T. Body; D. Silvagni; O. Grover; A.E. Hubbard; A. Cavallaro; M. Wigram; A.Q. Kuang; et al. (Nuclear Fusion)
The separatrix operational space (SepOS) model (Eich and Manz 2021 Nucl. Fusion 61 086017) is shown to predict the L–H transition, the L-mode density limit, and the ideal magnetohydrodynamic ballooning limit in terms of separatrix parameters for a wide range of Alcator C-Mod plasmas. The model is tested using Thomson scattering measurements across a wide range of operating conditions on C-Mod, spanning $\overline{n}_{e} =$ 0.3–5.5 $× 10^{20}\,$ m ^−3 , $B_{t} = 2.5$ –8.0 T, and $B_{p}$ = 0.1–1.2 T. An empirical regression for the electron pressure gradient scale length, $λ_{{p}_{e}}$ , against a turbulence control parameter, $α_{t}$ , and the poloidal fluid gyroradius, $ρ_{s,p}$ , is constructed for H-modes and found to require positive exponents for both regression parameters, indicating turbulence widening of near-scrape-off layer widths at high $α_{t}$ and an inverse scaling with $B_{p}$ , consistent with results on ASDEX Upgrade. The SepOS model is also tested in the unfavorable drift direction and found to apply well to all three boundaries, including the L–H transition as long as a correction to the Reynolds energy transfer term, $α_RS \lt 1$ is applied. I-modes typically exist in the unfavorable drift direction for values of $α_{t} \lesssim 0.3$ . Finally, an experiment studying the transition between the Type-I ELMy and EDA H-mode is analyzed using the same framework. It is found that a recently identified boundary at $α_{t} = 0.55$ excludes most EDA H-modes but that the balance of wavenumbers responsible for the L-mode density limit, namely $k_EM = k_RBM$ , may better describe the transition on C-Mod. The ensemble of boundaries validated and explored is then applied to project regime access and limit avoidance for the SPARC primary reference discharge parameters.